GAMBARAN PENULISAN KARYA TULIS ILMIAH WIDYAISWARA BDLHK KADIPATEN - Urfi Izzati (Jurnal Kewidyaiswaraan, 2021)
Writing of scientific papers is main task of widyaiswara beside educational activities that must do to develop their profession. According to the regulations, the writing of scientific papers credit number must also be fulfilled by widyaiswara for the preferment to promotion. Widyaiswara often neglects the writing of scientific papers, and even often becomes an obstacle to promotion. Research on the widyaiswara’s writing of scientific papers has never been carried out at BDLHK Kadipaten, even though the description of scientific papers writing needs to be known to develop the widyaiswara profession. This study aims to determine the description of scientific papers writing of widyaiswara BDLHK Kadipaten which includes submitting writing scientific papers in Dupak, obtaining scientific papers credit numbers, and writing scientific papers of widyaiswara. This research is a descriptive study with quantitative and qualitative methods. Data obtained from questionnaires and documentation studies, then analyzed by descriptive statistics. The results showed that in applying for scientific papers in Dupak, 53.33% of widyaiswara submitted their submission of scientific papers not being assessed and 59.19% of widyaiswara submitted scientific papers in each Dupak assessment period; widyaiswara's credit number from scientific papers shows that the average acquisition above 4/individual/year is 46.67%, there are 20% widyaiswara who have occupied their position for more than 4 years, and 46.67% stated that their promotion is delayed due to lack of credit score for scientific papers; the writing of scientific papers is still relatively lacking in international scientific papers (journals, proceedings, papers in scientific meetings), books, journal papers, papers in national scientific meetings, and proceedings paper. Based on these results, it shows that the writing of scientific papers by Widyaiswara BDLHK Kadipaten still needs to be improved to develop their profession. With this research, it is hoped that it will encourage widyaiswara to improve their ability and motivation in writing of scientific papers and will further increase the support of BDLHK Kadipaten institution to develop the profession of widyaiswara, especially in writing of scientific papers so as to increase widyaiswara’s competences and further improve performance of the institution.